A comparative study of localized phosphorus application and broadcasting method on biomass production and their use efficiency on Chilli (Capsicum annuum) under alkaline soil - Swain, Sanatan Kumar; Kalidas-Singh, Sagolshem; Puyam, Anita; Thakuria, Dwipendra; Maimom, Soniya; Zhiipao, R. Rustum; Debnath, Ashim; Bhuyan, Samikhya; Homeshwari-Devi, Mayanglambam; Huidrom, Sangeeta; Tsomu, Thupten; Umbrey, Yashi; et al. (Frontiers in Plant Science, 2024)
Rhizospheric based phosphorus (P) fertilizer management is necessary for crop production due to environmental concerns caused by the overuse of the broadcasting method and limited P reserves. This study proposes a comparison of P management that enhances P nutrition in Chilli (variety: Arka Khyati) through seedling root-dipping (SRD) in P-enriched slurry (SSPamended; pH of 8.1), micro-dose placement (MDP; drill and place closer to plant root), and full dose (187.6 mg kg -1 ) placement by broadcasting (FD). In SRD, seedlings were dipped in five different P concentrations (50, 100, 200, 300, and 400 mg P2O5 kg -1 ) for varying durations (0, ½, 1, 2, 3, and 4 hours) and transplanted into pots (dipping in 0 mg P2O5 kg -1 consider as control), along with the MDP and FD treatments (total 33 treatments with 5 replications). [Seedlings dipped in 200, 300, and 400 mg P2O5 kg -1 died within a week after transplanting, thus were excluded from further analysis]. The amount of P received in MDP and FD were 21-90 times higher than P adhesion to seedling roots in SRD treatments. Root volume was in order SRD>MDP>FD. Seedlings dipped in 100 mg P2O5 kg -1 for 2 hours in SRD exhibited the highest biomass production, P-use and -recovery efficiency; and showed an increase of 52%, 178%, and 293% in FD, MDP, and SRD compared to the control respectively. It is recommended to use the SRD method with other P sources in reduced amount to maintain the native P pool in soil, and further multilocational trials are needed to validate.